ANATOMIC PREREQUISITES OF THE SURGICAL THERAPY OF VAGINAL PROLAPSE AFTER HYSTERECTOMY - Jabůrek, Ladislav; Jabůrková, Jana (Biomedical papers, 1999)
The prolapse of vaginal stub occurs in about 4 % of hysterectomised patients. Suspension of vaginal stub on theligamentum sacrospinale dextrum is an effective method of the surgical management. The vaginal approach putsincreased demands on handiness and orientation in the operation field. Using a proper operation technique andperfect knowledge of the anatomic situation in fossa ischiorectalis can minimize the increased risk of bleedingduring the fixation, which results from frequent and varied anastomoses of pelvic vessels. The authors measuredseveral parameters on the group of pelvic girdles of 32 females and found following results:the distance between the base and the apex of spina ischiadica (17.1 mm); the distance between spina ischiadica andthe lateral margin of the os sacrum in the axis of central fibres of ligamentum sacrospinale (29.8 mm); the lenght ofaxial fibres of ligamentum sacrospinale (37.2 mm); the longest (11.2 mm) and the shortest (1.3 mm) diameter of15 mm from the top of spina ischiadica. In this site the thickness of muscular layer of musculus coccygeus (3.2 mm)has also been measured. The anatomic study can facilitate the introduction and implementation of more complexsurgical techniques.
Keywords: Ligamentum sacrospinale / Vaginal prolapse / Hysterectomy.